2004
DOI: 10.1063/1.1739287
|View full text |Cite
|
Sign up to set email alerts
|

Insights into “near-frictionless carbon films”

Abstract: On the induced microstructure changes of the amorphous carbon nitride films during annealing Electron cyclotron resonance deposition, structure, and properties of oxygen incorporated hydrogenated diamondlike amorphous carbon films A form of hydrogenated diamond-like-carbon, ''near-frictionless carbon,'' developed at Argonne National Laboratory has been studied by several spectroscopic techniques to determine the hydrogen content and carbon bonding within the film. The techniques used include hydrogen forward s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…For the 50/50 gas ratio in the plasma, we can note that hydrogen and deuterium are incorporated in the layer with a constant ratio D/H of 0.20. This is in good agreement with other works [17]. H+D content decreases linearly from 31 to 23 at.%.…”
Section: Hydrogen and Deuterium Rate Determinationsupporting
confidence: 94%
“…For the 50/50 gas ratio in the plasma, we can note that hydrogen and deuterium are incorporated in the layer with a constant ratio D/H of 0.20. This is in good agreement with other works [17]. H+D content decreases linearly from 31 to 23 at.%.…”
Section: Hydrogen and Deuterium Rate Determinationsupporting
confidence: 94%
“…Earlier hydrogen forward scattering studies on NFC films suggested that hydrogen concentrations range from 38 to 40 at.% [20]. We feel that such a high hydrogen concentration is primarily responsible for the superlow friction of these films beyond the initial or break-in friction regimes during sliding tests.…”
Section: Resultsmentioning
confidence: 64%
“…Specifically, they are synthesized in gas discharge plasmas that typically consist of ten hydrogen atoms per carbon atom. Under such deposition conditions, the resultant films contain higherthan-normal hydrogen concentrations (38-40 at.%) [20]. Most of the hydrogen atoms are paired with r-bonds of carbon atoms, but some unbonded or free hydrogen may also be present in the bulk, and they are accommodated as interstitials [2].…”
Section: Resultsmentioning
confidence: 99%
“…When it was observed for the first time, the purity of the C 2 D 2 gas used in the experiment was mentioned as one of the possible reasons for the differences revealed by IR spectroscopy [9]. In the last few years many experiments reporting differences in the incorporation of hydrogen and deuterium were published [10,11]. Differences in the deposition rate, smaller for films deposited from CD 4 than CH 4 , keeping fixed all other deposition parameters were also observed [12], indicating that further investigations are still needed.…”
Section: Introductionmentioning
confidence: 99%